Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/su11133557
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Land Use Management Needed to Conserve the Dragon’s Blood Tree of Socotra Island, a Vulnerable Endemic Umbrella Species

Abstract: Unsustainable overgrazing is one of the most important threats to the endemic and endangered population of dragon’s blood tree (Dracaena cinnabari) on Socotra Island (Republic of Yemen). However, there is a lack of information about the exact population size and its conservation status. We estimated the population size of D. cinnabari using remote sensing data. The age structure was inferred using a relationship between crown projection area and the number of branch sections. The conservation importance of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 55 publications
3
59
0
Order By: Relevance
“…This study demonstrated that D. cinnabari was a suitable habitat for half of the native reptile community of Socotra Island, but we could not disregard the occurrence of other unexplored endemic fauna living in the bark and canopy of the tree species. Although few trees have been proposed as umbrella species (however, see [19,25]), we supported the consideration of D. cinnabari as an umbrella species for vertebrates as well. This was due to its ecological, environmental, and evolutionary functions for the Socotra endemic reptiles, in addition to its historical economic and social role for local people that harvest D. cinnabari resin, which is an activity that could be sustainable if carefully regulated.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study demonstrated that D. cinnabari was a suitable habitat for half of the native reptile community of Socotra Island, but we could not disregard the occurrence of other unexplored endemic fauna living in the bark and canopy of the tree species. Although few trees have been proposed as umbrella species (however, see [19,25]), we supported the consideration of D. cinnabari as an umbrella species for vertebrates as well. This was due to its ecological, environmental, and evolutionary functions for the Socotra endemic reptiles, in addition to its historical economic and social role for local people that harvest D. cinnabari resin, which is an activity that could be sustainable if carefully regulated.…”
Section: Discussionsupporting
confidence: 81%
“…Although a significant part of the island was covered extensively with dragon's blood trees, their original range was reduced as a result of overgrazing and overmaturity (lack of natural regeneration and a large proportion of old and dead trees) [18]. Dracaena cinnabari meets the requirements for being considered an umbrella species [19] due to its size, shape, and distribution throughout Socotra, as well as its rarity and sensitivity to human disturbance [2]. Reptiles could be the target beneficiary taxon, as this tree was referred to as being occasionally used by some reptile species and the exclusive habitat of the Critically Endangered Hemidactylus dracaenacolus Rösler & Wranik, 1999 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, many authors have mentioned the lack of regeneration in dragon's blood tree forests and woodlands on Socotra [53,54]. Trees with heights of less than 2.9 m and diameters of less than 8 cm are absent, which supports the hypothesis of gradual extinction [9,16] over the hypothesis of sudden mass extinction [10]. There is a sufficient number of Dracaena trees available, with an average cover of 67 trees ha -1 .…”
Section: Population Structurementioning
confidence: 73%
“…According to Adolt et al [14], the mortality was less than 1% (0.82%), but this study showed four times higher mortality, reaching 3.41%. Additionally, a study published by Maděra et al [9] estimated that the mortality was less than 1%, which differed substantially with the age of the trees. Despite the long-term morphological, anatomical, and physiological adaptations of the DC trees to arid climate conditions [22,[28][29][30]32,55], the present tree populations do have an evidently unbalanced age structure with a largely disorganized woodland structure and a lack of natural regeneration [16].…”
Section: Population Structurementioning
confidence: 99%
See 1 more Smart Citation